2015
DOI: 10.1051/0004-6361/201526008
|View full text |Cite
|
Sign up to set email alerts
|

One of the closest exoplanet pairs to the 3:2 mean motion resonance: K2-19b and c

Abstract: Aims. The K2 mission has recently begun to discover new and diverse planetary systems. In December 2014, Campaign 1 data from the mission was released, providing high-precision photometry for ∼22 000 objects over an 80-day timespan. We searched these data with the aim of detecting more important new objects. Methods. Our search through two separate pipelines led to the independent discovery of K2-19b and c, a two-planet system of Neptune-sized objects (4.2 and 7.2 R ⊕ ), orbiting a K dwarf extremely close to t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 110 publications
(122 reference statements)
2
35
0
Order By: Relevance
“…Sinukoff et al (2016) reported the detection of 11 multiplanetary systems from K2 Campaigns 1 and 2. However, there are few such systems around nearby stars (Armstrong et al 2015;Crossfield et al 2015;Gandolfi et al 2017), and only a handful around brighter stars that are suitable for spectroscopic characterization.…”
Section: Introductionmentioning
confidence: 99%
“…Sinukoff et al (2016) reported the detection of 11 multiplanetary systems from K2 Campaigns 1 and 2. However, there are few such systems around nearby stars (Armstrong et al 2015;Crossfield et al 2015;Gandolfi et al 2017), and only a handful around brighter stars that are suitable for spectroscopic characterization.…”
Section: Introductionmentioning
confidence: 99%
“…K2 has so far unveiled many planetary systems with distinguishing characteristics, including a compact multi-planet system with sub-Saturn-mass planets in 3:2 mean motion resonance (Armstrong et al 2015), multiple systems with Earth-to super-Earth-sized planets around rather bright M dwarfs Petigura et al 2015), and a disintegrating minor planet around a white dwarf . In order to fully exploit the worldwide ground facilities for K2 follow-ups, we started the ESPRINT (Equipo de Seguimiento de Planetas Rocosos Intepretando sus Transitos) collaboration, which aims to discover and characterize unique transiting planets unveiled by K2.…”
Section: Introductionmentioning
confidence: 99%
“…The first results from K2 have now been published and it seems like the predictions before implementing the mission have been met or even superseded (Barros et al 2015;Narita et al 2015;Armstrong et al 2015;Becker et al 2015).…”
Section: Corot and Keplermentioning
confidence: 90%